Inability to Be Self-reliant' as an Indicator of U.S. Poverty: Measurement, Comparisons, and Implications - Robert Haveman; Andrew Bershadker (Levy Economics Institute of Bard College, 1998)
Given the current emphasis in national policy on self-reliance and a smaller role for government, the official poverty measure, which is based on the premise that all families should have sufficient income from either their own efforts or government support to boost them above a family-size-specific threshold, appears to have less policy relevance now than in prior years. We present here a new concept of poverty based on self-reliance, that is, the ability of a family, using its own resources, to support a level of consumption in excess of needs. Using a measure of net earnings capacity (NEC) to examine the size and composition of the self-reliant-poor population from 1975 to 1995, we find that self-reliance poverty has increased more rapidly than has official poverty. We find that families commonly thought to be the most impoverished–those headed by minorities, single women with children, and individuals with low levels of education–have the highest levels of self-reliance poverty, but have experienced the smallest increases in this poverty measure. Families commonly thought to be economically secure–those headed by whites, men, married couples, and highly educated individuals–have the lowest levels of self-reliance poverty, but have experienced the largest increases. We speculate that the trends in self-reliance poverty stem largely from underlying trends in the United States economy, in particular the relative decline of wage rates for whites and men and the rapidly expanding college-educated demographic group.
Keywords: 330